The Role of Diet and Gut Microbiota in Regulating Gastrointestinal and Inflammatory Disease - Gill, Paul A.; Inniss, Saskia; Kumagai, Tomoko; Rahman, Farooq Z.; Smith, Andrew M. (Frontiers in Immunology, 2022)
Diet is an important lifestyle factor that is known to contribute in the development of human disease. It is well established that poor diet plays an active role in exasperating metabolic diseases, such as obesity, diabetes and hypertension. Our understanding of how the immune system drives chronic inflammation and disease pathogenesis has evolved in recent years. However, the role of diet in contributing to inflammatory conditions such as inflammatory bowel disease, multiple sclerosis and arthritis is not as well defined. The western diet has been associated as pro-inflammatory, in contrast to traditional dietary patterns that are associated as being anti-inflammatory. This may be due to direct effects of nutrients on immune cell function. Diet may also affect the composition and function of gut microbiota, which consequently affects immunity. In animal models of inflammatory disease, diet may modulate inflammation in the gastrointestinal tract and in other peripheral sites. Despite limitations of animal models, there is now emerging evidence to show that anti-inflammatory effects of diet may translate to human gastrointestinal and inflammatory diseases. However, appropriately designed, larger clinical studies must be conducted to confirm the therapeutic benefit of dietary therapy.